Impact of a reconstructive stage on the postoperative course in patients with oral cancer - A. A. Boyko; A. V. Karpenko; E. M. Trunin; R. R. Sibgatullin; N. S. Chumanikhina; O. M. Nikolaeva; I. A. Togo; M. G. Kostova (Опухоли головы и шеи)
The study objective is to assess effect of the reconstructive stage on the course of the postoperative period in patients with oral cancer.Materials and methods. A retrospective analysis of medical records of 174 patients (121 men and 53 women) aged 36 to 84 years (average 58.26 ± 8.72 years) with oral cancer undergoing treatment from January 2009 to June 2016 was performed. Depending on the nature of the reconstructive stage, the patients were divided into 3 groups. The group 1 consisted of 59 patients, to eliminate the defects of which flaps were taken on axial blood supply, the group 2 included 83 patients who had a reconstructive phase of the operation included a microsurgical reconstruction; 32 patients who had not used additional plastic material to eliminate the defect made up the control group. The following parameters were taken as evaluation parameters: the duration of the operation and hospitalization, the time spent in the intensive care unit, the frequency of serious and frivolous complications. The criterion for distinguishing serious and unserious complications is the fact that the patient returned to the operating room.Results. The reconstructive stage increased the operation duration by 72.12 min in the group 1 and by 285.72 min in the group 2, the length of stay in the intensive care unit – by 0.67 and 2.58 days, respectively, the hospital stay – by 33.9 and 40.4 %. The incidence of complications was higher in the groups 1 and 2 than in the control (6.6 %), and the type of reconstruction had almost no effect on it (42.37 % in the group 1 and 38.55 % in group 2). The frequency of serious complications was higher in the group 2, the frequency of partial flap necrosis – in the group 1.Conclusion. The inclusion of a reconstructive stage into the protocol of surgical treatment for oral cancer is absolutely reasonable, because it gives the patients a chance to return to their normal lives. Microsurgical reconstruction is a costly and labour-consuming procedure; however, it has almost the same number of complication as reconstructive surgery with flaps with an axial blood supply.